Analysing design components in mix media cultural preservation documentary culminating in word cloud - Mohd Damanhuri, Nur Batrisyia; Mohd Lazim, Nur Aniza; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
In today’s digital world, keeping cultural heritage alive needs more than just traditional documentary styles. With fast changes in technology and the strong pull of digital media, many young people don’t realize they are slowly losing touch with their cultural roots. They often follow global trends and live in a digital lifestyle that makes traditional values and practices feel far away. This journal looks at ten mixed media cultural documentaries and focuses on the design components used like the elements of design, photography, images, video, animation, sound, and typography. The goal is to see how these tools can help make cultural stories feel more real, interesting, and easier to understand for the younger generation. The findings show that when these mixed media elements are combined well, they can improve storytelling and help people connect better with what they see. However, helping youth understand and appreciate culture is not simple. It takes more than just good visuals it also needs smart ideas, content that feels close to their daily lives, and something they can feel emotionally. Mixed media has a lot of potential to do this, but it must be done with care, so the message reaches young people in a way that truly matters.